Chk1 phosphorylates the tumour suppressor Mig-6, regulating the activation of EGF signalling - Liu, Ning (Nature Publishing Group, 2012)
The tumour suppressor gene product Mig-6 acts as an inhibitor of epidermal growth factor (EGF) signalling. However, its posttranslational modifications and regulatory mechanisms have not been elucidated. Here, we investigated the phosphorylation of human Mig-6 and found that Chk1 phosphorylated Mig-6 in vivo as well as in vitro. Moreover, EGF stimulation promoted phosphorylation of Mig-6 without DNA damage and the phosphorylation was inhibited by depletion of Chk1. EGF also increased Ser280-phosphorylated Chk1, a cytoplasmic-tethering form, via PI3K pathway. Mass spectrometric analyses suggested that Ser 251 of Mig-6 was a major phosphorylation site by Chk1 in vitro and in vivo. Substitution of Ser 251 to alanine increased inhibitory activity of Mig-6 against EGF receptor (EGFR) activation. Moreover, EGF-dependent activation of EGFR and cell growth were inhibited by Chk1 depletion, and were rescued by co-depletion of Mig-6. Our results suggest that Chk1 phosphorylates Mig-6 on Ser 251, resulting in the inhibition of Mig-6, and that Chk1 acts as a positive regulator of EGF signalling. This is a novel function of Chk1.